Natural convection in a square inclined enclosure with vee-corrugated sidewalls subjected to constant flux heating from below - Hussain, Salam Hadi Hadi; Hussein, Ahmed Kadhim Kadhim; Mahdi, Mahmoud Moustafa Moustafa (Nonlinear Analysis: Modelling and Control, 2011)
Two-dimensional steady natural convective flow in a square inclined enclosure with vertical vee-corrugated sidewalls and horizontal top and bottom surfaces has been numerically studied. A discrete heat flux strip of 24% of the total length is flush-mounted on the bottom wall, while the other non-heated parts of the bottom wall and the top wall are considered adiabatic. The two vee-corrugated sidewalls are maintained at constant cold temperature. Grashof number is varied from 103 to 106, corrugation frequency is varied from 0.5 to 2.0, corrugation amplitude has been fixed at 10% of the enclosure height and the enclosure inclination angle is varied to 0◦, 10◦, 20◦ and 30◦ respectively. The enclosure is filled with air (Pr = 0.71). The flow has been assumed to be steady and laminar. Fluid properties have been assumed constant except for the density change with temperature that gives rise to the buoyancy forces. The solution has been obtained using the governing equations written in terms of dimensionless variables. The dimensionless governing equations are solved using finite volume method. Results are presented in the form of streamline and isotherm plots. The results of the present work show that the natural convection phenomenon is greatly affected by increasing the enclosure inclination angle. The variation in the average Nusselt number at the bottom wall, where the heat source exists and the maximum dimensionless temperature are also presented. The results are compared and found to be in a good agreement with other published results.